Detection of Citrullinated Fibrin in Plasma Clots of Rheumatoid Arthritis Patients and Its Relation to Altered Structural Clot Properties, Disease-Related Inflammation and Prothrombotic Tendency - Bezuidenhout, Johannes A.; Venter, Chantelle; Roberts, Timothy J.; Tarr, Gareth; Kell, Douglas B.; Pretorius, Etheresia (Frontiers in Immunology, 2020)
Aims. The risk of cardiovascular events in patients with Rheumatoid Arthritis (RA) is disproportionately heightened as a result of systemic inflammation. The relative effect of autoimmune-associated citrullination on the structure and thrombotic potential of fibrin(ogen) remains unknown. We therefore compared indices of vascular function, inflammation, coagulation and fibrin clot composition in RA patients with healthy controls and evaluated parameter association with disease presence. Methods. Blood samples were collected from 30 RA patients and 30 age- and gender-matched healthy volunteers. Levels of SAA, CRP, ICAM-1 and VCAM-1 was measured using a sandwich immunoassay. Whole blood coagulation was assessed using Thromboelastography (TEG®). Fibrin clot networks and fiber structure was investigated using Scanning Electron Microscopy. The detection and quantification of citrullination in formed fibrin clots were performed using a fluorescently labeled Citrulline monoclonal antibody with Fluorescence Wide Field Microscopy. Results. Concentrations of SAA, CRP and ICAM-1 were significantly elevated in RA patients compared to controls. TEG parameters relating to coagulation initiation, rate of fibrin cross-linking, and time to reach maximum thrombus generation were attenuated in RA patients.. Microscopic analysis revealed denser networks of thicker fibrin fibers in RA patients compared to controls and multiple citrullinated regions within fibrin clot structures in RA patients were present. Conclusion. Our findings provide novel evidence for the citrullination of fibrin within vasculature is more prominent in RA plasma compared to control plasma and plasma is more accessible than synovial fluid. Citrullinated fibrinogen could play a role as a determinant of thrombotic risk in RA patients.